2010
DOI: 10.1111/j.1365-2427.2010.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genetic diversity and gene flow of common carp from main river drainages in China

Abstract: Summary 1. The common carp (Cyprinus carpio L.) is one of the most widely distributed and important freshwater fishes in the world. In China, the common carp has been recognised as three subspecies: C. carpio haematopterus, C. carpio rubrofuscus and C. carpio carpio. The Nanling Mountains have been suggested as providing the dividing line between C. carpio haematopterus and C. carpio rubrofuscus. However, the demographic history and gene flow of the common carp in China is not clear. 2. We collected mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…2a). Also, recent studies have indicated that human-mediated translocation of carp across Chinese drainage basins has likely resulted in high levels of gene flow preventing clear identification of the three postulated sub-species C. c. carpio, C. c. haematopterus and C. c. rubrofuscus (an endemic cultured sub-species from that area (Wang et al 2010). Finally, reference to domesticated varieties as C. c. domestica as well as e.g.…”
Section: Originmentioning
confidence: 99%
“…2a). Also, recent studies have indicated that human-mediated translocation of carp across Chinese drainage basins has likely resulted in high levels of gene flow preventing clear identification of the three postulated sub-species C. c. carpio, C. c. haematopterus and C. c. rubrofuscus (an endemic cultured sub-species from that area (Wang et al 2010). Finally, reference to domesticated varieties as C. c. domestica as well as e.g.…”
Section: Originmentioning
confidence: 99%
“…Genetic evidence indicates that all common carp populations originate from two ancestral forms of wild carp, the European subspecies ( C. c. carpio ) and the East Asian subspecies ( C. c. haematopterus ) (Chistiakov and Voronova, 2009). The validity of a third subspecies, C. c. rubrofuscus , is questionable; it may have diverged from C. c. haematopterus (Zhou et al, 2004; Wang et al, 2010; Kohlmann and Kersten, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These factors combined with accumulation of mutations and long-term geographical isolation have produced many varieties of common carp with distinct skin color, body shape, scale pattern, body size, and stress tolerance. Human transport of carp to different geographical locations has generated high levels of gene flow (Wang et al, 2010). Hybrid breeding of carp in China has been common over the last 50 years and has resulted in many varieties or strains, such as Jian carp (JIAN).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the 1,200-year-old rice-fish system of Qintian county, Zhejiang Province, was listed as one of the "Globally Important Agricultural Heritage Systems (GIAHS)" by the Food and Agriculture Organization of the United Nations in 2005 1 (Xie et al, 2011). PF-carp farming in the GIAHS rice-fish system named Oujiang carp has been practiced and passed down for generations (Wang, 1997). Within the Qintian GIAHS site, rice-fish farmer households exchange fry and parental carp for their own rice-fish production, thereby contributing to a high rate of gene flow and high genetic diversity of PF-carp (Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%